Factors associated with long COVID syndrome in a Colombian cohort - Martínez-Ayala, María Camila; Proaños, Nadia Juliana; Cala-Duran, Julian; Lora-Mantilla, Alvaro Jose; Cáceres-Ramírez, Catalina; Villabona-Flórez, Silvia Juliana; Camacho-López, Paul Anthony (Frontiers in Medicine, 2023)
Introduction After acute phase of SARS-CoV-2 infection, some patients persist with clinical symptoms, a phenomenon known as Long COVID syndrome. It is necessary to understand the factors associated with the persistence of these symptoms to develop individualized preventive approaches and effectively address this challenge. Objective To determine the factors associated with the persistence of symptoms six months after COVID-19 infection. Materials and methods A ambidirectional cohort, single-center study, that included individuals previously diagnosed with COVID-19 by real-time polymerase chain reaction (PCR) positive test, who were followed for a period of six months. Univariate, bivariate and a multivariate binomial regression model were performed to determine risk factors associated with the persistence of COVID-19 symptoms at the six months of follow-up. Results The prevalence of long COVID syndrome was 47%. Age demonstrated no significant association with Long COVID (RR 0.999 [95% CI 0.996–1.002]); however, female sex (RR 1.148 [95% CI 1.038–1.268]), requirement of mechanical ventilation (RR 1.278 [95% CI 1.050–1.555]), presence of Chronic Obstructive Pulmonary Disease (COPD) (RR 1.340 [95% CI 1.104–1.626]), Rheumatic Disease (RR 1.259 [95% CI 1.055–1.504]) and the Hospitalization Type: General Hospitalization (RR 1.247 [95% CI 1.090–1.427]) and ICU Hospitalization (RR 1.490 [95% CI 1.221–1.818]) were significantly associated with the persistence of symptoms at the six month of follow-up. Conclusion Female sex, presence of COPD, rheumatic disease, hospitalization type and requirement of mechanical ventilation during index infection were identified as significant risk factors for the diagnosis of Long COVID. These findings emphasize the importance of addressing Long COVID syndrome in terms of prevention and management, taking these risk factors into consideration.